The Impact of Hypermobile “Ehlers-Danlos Syndrome” and Hypermobile Spectrum Disorder on Interpersonal Interactions and Relationships - De Baets, Stijn; De Temmerman, Marieke; Calders, Patrick; Malfait, Fransiska; Van Hove, Geert; Vanderstraeten, Guy; De Wandele, Inge; Van de Velde, Dominique (Frontiers in Rehabilitation Sciences, 2022)
Background: People with Ehlers-Danlos Syndromes and Hypermobility Spectrum Disorders are hampered in their social participation, especially in the social relationships they have. Objective: The aim of this study is to research the impact of hypermobile Ehlers-Danlos Syndrome (hEDS) and Hypermobile Spectrum Disorders (HSD) on interpersonal interactions and relationships. Methods: A phenomenological hermeneutic study was performed. Semi-structured interviews were used to explore the experiences of 11 participants. Results: Four themes emerged from the data analysis. (1) people with hEDS or HSD can no longer do what they want to do and that affects their identity, (2) people with hEDS or HSD have to find a balance in the amount of activities they participate in, (3) having hEDS or HSD influences how to ask for, accept and give help, and (4) Relationships are affected in persons with hEDS or HSD. As well as changes in the social network, different types of relationships are influenced by the disease, including relationship with their partner, their children, their friends, strangers, fellow-sufferers and health care professionals.